Pengaruh Kemampuan Berpikir Kreatif Terhadap Kemampuan Mengelolah Lingkungan Hidup dengan Pendekatan Berbasis Masalah pada Matakuliah PKLH: Effect of Creative Thinking Skills on Ability to Manage the Environment with Problem-Based Approach in PKLH Course - Ahmad, Deni Nasir (SEJ (Science Education Journal), 2019)
The purpose of the research activity is to know whether there is an influence of the ability to think creatively on the ability to manage the environment with a problem-based approach to the PKLH course. The method in this study is a quasi-experimental method, the sample in research activities is physics education students, namely R4A class totaling 29 people. While the data collection techniques used in this study are questionnaires given to determine students 'creative thinking abilities and scoring instruments from student scientific reports to determine students' abilities in managing the environment. The simple linear regression test was used to examine the research hypothesis. The results showed that there was an indirect effect between the ability to think creatively on the ability to manage the environment with independent assignments in the PKLH courseshown from the hypothesis test that is fcount <ftabel that is equal to 0.139 <3.37.